Population Estimate, Habitat-Use and Activity Patterns of the Honey Badger in a Dry-Deciduous Forest of Central India - Chatterjee, Nilanjan; Nigam, Parag; Habib, Bilal (Frontiers in Ecology and Evolution, 2020)
Studies on carnivores are skewed towards large carnivores in India, limiting ecological information of the smaller ones. Basic ecological understanding like population density, distribution, habitat-use patterns of small carnivores is lacking. This inadequate knowledge has led to disagreement between conservation approaches in different landscapes. Honey badgers (Mellivora capensis) are cryptic carnivores distributed across large areas of Africa and Asia; however, fundamental ecological knowledge is scarce. The species is thought to exist at low population densities throughout its range. We used a large camera trap dataset from a tiger reserve in Maharashtra State, India to understand the population density, habitat preference and diel activity pattern of the species. We applied an extension of the spatial count model for the estimation of population. Habitat preference analyses were carried out using generalized linear models and activity patterns were analyzed using kernel-density functions. Population density was estimated as 14.09 (95% CI 10-22.25) individuals per 100 km2. Habitat use revealed a positive association with forest cover and negative association with elevation. This may expose the species to other large carnivores in the habitat but honey badger activity pattern peaked at midnight retaining minimum temporal overlap with other large carnivores (e.g. tiger Panthera tigris, leopard Panthera pardus, dhole Cuon alpinus) and moderate-overlap with small carnivores (e.g. jungle cat Felis chaus, rusty-spotted cat Prionailurus rubiginosus). These behaviours, in turn, may facilitate the species to exist at such high density even with high carnivore density. We hope the findings of this study will fill the existing knowledge gap of this species and aid in guiding the conservation of the species in other landscapes and reserves.